Front Cover: Pt–Co Alloy Nanoparticles on a γ‐Al2O3 Support: Synergistic Effect between Isolated Electron‐Rich Pt and Co for Automotive Exhaust Purification (ChemPlusChem 5/2019). Issue 5 (18th March 2019) - Sato, Katsutoshi; Ito, Ayano; Tomonaga, Hiroyuki; Kanematsu, Homare; Wada, Yuichiro; Asakura, Hiroyuki; Hosokawa, Saburo; Tanaka, Tsunehiro; Toriyama, Takaaki; Yamamoto, Tomokazu; Matsumura, Syo; Nagaoka, Katsutoshi
Abstract : The front cover shows the proposed mechanism for automotive exhaust purification over a Pt–Co alloy nanoparticle catalyst with an extremely low Pt/Co molar ratio. In the catalyst, the isolated electron‐rich Pt atoms are present on the surface the nanoparticles and play an important role in NO x capture and activation, which are important elementary steps in exhaust purification. Details are given in the Full Paper by K. Sato, K. Nagaoka et al. onpage 447 in Issue 5, 2019 (DOI:10.1002/cplu.201800542 ).